Treatment of hepatic hydratic cyst. Actual state. - Torres Amorín, Marcos (Cirugía del Uruguay, 2002)
In this paper we have included an updated ana!ysis of treatment far patients suffering form hydatic cyst of liver and preferred surgica! treatment with reference to the various evolutive foms of liver hydatidosis and its comp!ications afecting the main bi/iary tract. !t a/so contains a summary of sero!ogic studies and scanning procedures, as we/1 as description of medica! treatment. The criteria applied fo!lows Larghero's surgica! procedure, aimed at treatment of parasite, adventitia and !esions of tissues where it attaches itse/f. There is a/so a review of conservative, c!assic but still va/id techniques, micro invasive techniques and radical resection treatments.